Four years analysis of helicobacter pylori infection among patients with dyspeptic at Universiti Kebangsaan Malaysia Medical Centre - Alfizah H,; Rizal AM,; Isa MR,; Aminudin A,; Jasmi AY,; Ramelah M, (Penerbit UKM, 2010)
Helicobacter pylori has been implicated as an aetiologic agent for type B chronic gastritis, peptic ulcer and gastric cancer. It is considered the most common bacterial infection in the world with approximately 50% of the population being infected. The majority of infected individuals are asymptomatic, with some developing gastritis only. However, chronic infection with H. pylori without antibiotic treatment predisposes infected individuals to the development of gastric cancer. The aim of this study is to determine active H. pylori infection among patients with symptoms of dyspepsia using three combinations of diagnostic methods. In this report, we studied 1,376 consecutive patients who underwent upper gastrointestinal endoscopy at Universiti Kebangsaan Malaysia Medical Center (UKMMC) for dyspepsia from the period January 1999 to December 2002. The classification of patient’s diagnosis was assessed by endoscopic and histological examination. The H. pylori status was determined by rapid urease test, histological examination or H. pylori culture. Presence of H. pylori infection was confirmed in 30.8% of patients with dyspepsia. H. pylori infection was more prevalent in older patients and in males compared to females. Patients with severe gastroduodenal diseases were more commonly infected with H. pylori. There was a significant difference in H. pylori prevalence among the different ethnic groups. Indians had the highest infection rate (45.4%), followed by Chinese (36.8%) and the lowest were seen in Malays (18.3%). This finding on determination of active H. pylori infection among patients with dyspepsia is consistent with serological studies that showed racial differences in H. pylori prevalence. However, the pattern of H. pylori infection does not reflect the prevalence of severe gastroduodenal diseases among different ethnic groups.